Genre Based Approach (GBA) in Teacher's Module at Senior High School Phase E - Afriyanti, Rika; Puspita, Dela (Politeknik Negeri Bengkalis, 2023)
This research is written to describe the application of Genre Based Approach (GBA) in teaching English as the implementation Merdeka Curriculum at Senior High School. The objective of this research is to describe the ways of the teacher in implementing GBA in writing module for Senior High School grade X phase E. There are four cycles of GBA; BKOF, MOT, JCOT, and ICOT. These cycles became the focus of the implementation of GBA. Then, this research belongs to qualitative approach with content analysis as the method. Also, the researcher used document of teacherâ€™s module of grade X Phase E Senior High School as the source of data and then, the researcher also chose document analysis as the instrument to analyze the data. To analyze the data, the researcher used four steps; organizing and preparing the data, reading the data, coding the data and interpreting the data. After doing data analysis, the researcher found that the teacher only implemented three cycles, namely, BKOF, MOT, and ICOT. The teacher did not generate the ideas about JCOT cycle. In addition, the teacher still needs to improve knowledge, skill and competence in understanding GBA because the teacher did not implement the cycles in detail. Â Keywords: Genre Based Approach (GBA), Module.